The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.17221/254/2019-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness of Polish dairy farms in the European Union

Abstract: This article analyses the competitiveness of dairy farms in Poland in relation to selected EU countries. The competitive advantage of dairy farms was evaluated and compared based on remuneration for family labour. Two variants of the above indicator were calculated: (1) Remuneration for family labour (FL1) as the relationship between farm net income and the farmer’s unpaid labour input, and (2) Remuneration for family labour (FL2) as the relationship between farm net income minus the opportunity costs of own l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…When deciding on the choice of factors for the model, the ones that were most often identified as having an impact on work efficiency were selected. Authors dealing with this subject indicated the following indices: the size of farms (Giannakis and Bruggeman 2018;MacDonald et al, 2020;Parzonko and Bórawski, 2020), land resources per employee (Galluzzo, 2016;Giannakis and Bruggeman, 2018), capital per employee (Kusz and Misiak, 2017) and the intensity of production (Fuglie et al, 2017;Gołaś, 2019;Hayami, 1970;Yamada and Ruttan, 1980). Hence, the presentation of the level of operating subsidies in relation to the value added generated on the farm in the set of analysed factors will -as mentioned in the introductioncomplement the knowledge about the mechanisms of increasing labour productivity, and will also allow to verify to what extent operating subsidies are an important factor in achieving higher labour productivity.…”
Section: Methodsmentioning
confidence: 99%
“…When deciding on the choice of factors for the model, the ones that were most often identified as having an impact on work efficiency were selected. Authors dealing with this subject indicated the following indices: the size of farms (Giannakis and Bruggeman 2018;MacDonald et al, 2020;Parzonko and Bórawski, 2020), land resources per employee (Galluzzo, 2016;Giannakis and Bruggeman, 2018), capital per employee (Kusz and Misiak, 2017) and the intensity of production (Fuglie et al, 2017;Gołaś, 2019;Hayami, 1970;Yamada and Ruttan, 1980). Hence, the presentation of the level of operating subsidies in relation to the value added generated on the farm in the set of analysed factors will -as mentioned in the introductioncomplement the knowledge about the mechanisms of increasing labour productivity, and will also allow to verify to what extent operating subsidies are an important factor in achieving higher labour productivity.…”
Section: Methodsmentioning
confidence: 99%
“…Polish scientists investigating the competitiveness of dairy farms in the European Union also indicate that the scale of production has a significant level of impact on economic efficiency, including labor productivity, which may contribute to further consolidation of dairy farms and reduce their total number [12].…”
Section: E3s Web Of Conferences 282 07015 (2021) Efsc2021mentioning
confidence: 99%
“…Based on the empirical data of Germany F. Frick, J. Sauer investigated the bonds of deregulation and productivity and efficiency of redistribution of resources in the dairy sector [11]. Competitiveness of Polish Dairy Farms E European Union was an object of research Parzonko A., Bórawski P. [12].…”
Section: Introductionmentioning
confidence: 99%
“…Проблемам розвитку молочного скотарства в Україні присвячені праці багатьох вітчизняних науковців, зокрема: Л. Воляк (Voliak & Halitska, 2018), В. Колоша (Kolosha, 2018), В. Россоха (Rossokha & Petrychenko, 2018), С. Самайчук (Samaichuk, 2020), О. Чередніченко, О. Пащенко (Cherednichenko & Pashchenko, 2018) та інші. Дослідження щодо розвитку виробництва молока часто зустрічаються у працях зарубіжних науковців: A. Parzonko, P. Bórawski (Parzonko & Bórawski, 2020), M. Michaličková, Z. Krupová, P. Polák, L. Hetényi, E. Krupa (Michaličková et al, 2014), P. Kopeček (Kopeček, 2002), S. Pieralli, S. Hüttel, M. Odening (Pieralli et al, 2017), J. Sauer, U. Latacz-Lohmann (Sauer & Latacz-Lohmann, 2015) та інших.…”
Section: вступunclassified